Comparison of Formocresol and Ferric Sulfate Pulpotomy in Primary Molars: A Systematic Review and Meta-analysis - M. Fallahinejad Ghajari; N. Memar Kermani; MJ. Kharazi Fard; M. Vatanpour4 (Tehran University of Medical Sciences, 2009)
Objective: Several studies have compared ferric sulfate and formocresol pulpotomy in primary molars. The results of these studies, however, could not be compared due to differences in evaluated outcomes (clinical, radiographic, or histologic) and follow up duration. The aim of the present study was a systematic review of similar studies and a metaanalysis of their results to provide the latest evidence on the issue. Materials and Methods: Web-based search was done in EMBASE, Cochrane, Pubmed, Google Scholar, IranMedex, Scientific Citation Index (SCI), and Scopus index databases. A hand search also was conducted in scientific and research dental journals approved by the Ministry of Health and Medical Education of Iran. Eight randomized clinical trial articles were selected. Clinical success, clinical and radiographic success (total success) rate were assessed as outcome variables. Peto test served for data analysis. Results: The clinical success of formocresol pulpotomy was comparable to that of ferric sulfate (P=0.574). In addition, the difference between total success rate of the two methods in different studies was insignificant (P=0.42). Conclusion: No significant difference existed between the total success rate of formocresol and ferric sulfate pulpotomy, and ferric sulfate can be an appropriate alternative for formocresol.